Physical and Mechanical Characteristics of Coconut Coir-Based Composite Roof Tiles with Molasses Polyurethane Coating - Riskatul Walidaini; Dede Hermawan; Irsan Alipraja; Mahdi Mubarok; Rudi Hartono; Aprilia Kartikawati; Sukma Surya Kusumah; Jajang Sutiawan (Talenta Publisher, 2026)
Lightweight roofing materials based on natural fibers are one alternative for developing more efficient and sustainable building materials. Coconut coir is an abundant agricultural waste product with potential as a raw material for composite roof tiles. This study aims to evaluate the effect of molasses concentration variation on the physical and mechanical properties of coconut coir-based composite roof tiles coated with polyurethane. Composite roof tiles are produced from coconut coir particles and coated using a polyurethane system with varying molasses concentrations. Physical property testing included density, moisture content, water absorption, and thickness swelling, while mechanical properties were evaluated through flexural testing. All tests were conducted in accordance with JIS A 5908:2003 standards and analyzed using analysis of variance. The results showed that variations in molasses concentration in the polyurethane coating system did not have a statistically significant effect on the physical and mechanical properties of composite tiles. Polyurethane-molasses coating tended to reduce water absorption and thickness swelling compared to uncoated tiles, but did not show a consistent pattern of change. The mechanical properties of composite tiles were relatively similar across all treatments, indicating that tile performance is more influenced by the material's internal characteristics and the compaction process.